The Display of Gender Stereotypes in Armenians’ Concepts of Man and Woman. - Gargrstyan, Lilit (Bulletin of Yerevan University E: Philosophy, Psychology, 2018)
The article presents theoretical and empirical analyzesof main gender stereotypes. It discusses both the cross-cultural studies of gender stereotypes and their classification and the results of authors’ own study. The results of thequalitative study show that Armenians’ gender stereotypes mainly correspond with gender stereotypes revealed in different cultures, but there are also some stereotypical concepts that are specific to our culture.